Oral Immunization With Plant-Based Vaccine Induces a Protective Response Against Infectious Bursal Disease - Lucero, María Soledad; Chimeno Zoth, Silvina; Jaton, Juan; Gravisaco, María José; Pinto, Silvina; Richetta, Matías; Berinstein, Analía; Gómez, Evangelina (Frontiers in Plant Science, 2021)
Infectious Bursal Disease Virus (IBDV) is the etiological agent of an immunosuppressive and highly contagious disease that affects young birds causing important economic losses in the poultry industry worldwide. We have previously developed a plant-based vaccine candidate for Infectious bursal disease (IBD) that is able to protect against infection with IBDV when administered through intramuscular (im) route. Given that oral vaccination is non-invasive and stimulates immunity of the mucosal gastrointestinal surface, initial site of contact and entry of IBDV, the aim of this work was to study if our immunogen was also able to elicit a protective immune response when orally administered. We demonstrated that 85 % of the animals that received two oral doses of the vaccine formulation and all animals that were orally boosted after an im prime developed virus neutralizing antibodies and were protected against IBDV infection, evidenced by the BB ratio, absence of T cell infiltration and low viral load in bursa. Although mild to moderate bursal damage was observed in some of these animals, these lesions were not as severe as the ones observed in challenged control groups which also presented signs of acute inflammation, bursal atrophy, T cell infiltration and absence of viral clearance. These results show that two immunizations with our recombinant immunogen are able to induce a specific and protective immune response in chickens against IBDV when orally administered in a prime/boost scheme or when the oral boost follows an intramuscular prime. In conclusion, our oral plant-based vaccine candidate could represent a viable alternative to conventional vaccines and be of great interest for the poultry industry.